ANALISA MODEL ARUS JENUH PADA SIMPANG BERSINYAL (Studi Kasus : Jl. Drs. H. Abdullah Silondae – Jl. Syech Yusuf – Jl. Lawata) - Rudi Balaka; Wiwin Yudistira (STABILITA || Jurnal Ilmiah Teknik Sipil, 2018)
The amount of saturated flow is influenced by several factors, namely the effective approach width, traffic conditions and characteristics, side constraints, clogs, vehicle characteristics, city size. The method used in calculation of saturated current is Time Slice method and MKJI method 1997. The observed crossroads are junction jl. Drs. H. Abdullah Silondae – jl. Syech Yusuf – jl. Lawata. Data obtained from survey in the field will be analyzed by Time Slice method and MKJI method. The formula used in the MKJI method to calculate the maximum saturation current value is So = 600 x We, with the description We are the effective width of a path. From the results of the analysis performed on the intersection of signal at jl. Drs. H. Abdullah Silondae – jl. Syech Yusuf – jl. Lawata, not all arms are saturated. the saturated flow is only two sides of the intersection in the northern intersection with 3553 smps / hour, Time Slice method of 5.295 smp / 6 sec and the southern with the saturation value of 3518 smp / hour, Time Slice method 4,995 pcu / 6 sec while in the eastern and west sides of the intersection does not lead to saturated condition.